Privacy challenges in Enterprise 2.0 - Pettersen, Lene; Brandtzæg, Petter Bae (AoIR Selected Papers of Internet Research, 2012)
This study explores privacy challenges in Enterprise 2.0 (E2.0) in a large-scale multinational knowledge-intensive company. The study focuses on the dilemma of sociability vs. privacy likely to arise under E2.0 models, applying both social capital and privacy regulation theory. A qualitative approach has been selected to gain deeper insights into the interplay of E2.0 mechanisms, surveillance and privacy. This was done by using a comprehensive qualitative case study of 27 in-depth interviews and participatory observations of professional knowledge-workers using E2.0 at work in Norway, Denmark, UK and Morocco. Ethnographic field studies were conducted in Norway and Morocco in 2010 and 2011, with follow up studies in 2012. The results show that introducing E2.0 into the workplace is not without privacy risks. Many of the employees in this study report an experience of being monitored when using E2.0 and a fear of leaving digital footprints that the company can misuse. These results pinpoint the importance of balancing sociability, knowledge sharing and privacy in E2.0 solutions, as well as a firm understanding of different user needs in regards to privacy and trust. Different practices of using E2.0 often lead to both larger and visible gaps between employees (i.e., those who contribute and those who don’t), as well as different privacy concerns or dilemmas. As a privacy strategy, employees report to collaborate and interacts offline with co-workers. Finally, our study places the E2.0 dilemma on the agenda, and is one important contribution to the fairly unexplored field of social media migrating into global and electronically monitored workplaces, where spaces for privacy become increasingly blurred.